ELN and FBN2 Gene Variants as Risk Factors for Two Sports-related Musculoskeletal Injuries - Khoury, L. El; Posthumus, M.; Collins, M.; van der Merwe, W.; Handley, C.; Cook, J.; Raleigh, S. M. (International Journal of Sports Medicine, 2015)
The proteins ELN and FBN2 are important in extracellular matrix function. The ELN rs2071307 and FBN2 rs331079 gene variants have been associated with soft tissue pathologies. We aimed to determine whether these variants were predisposing factors for both Achilles tendinopathy (AT) and anterior cruciate ligament (ACL) ruptures. For the AT study, 135 cases (TEN group) and 239 asymptomatic controls were recruited. For the ACL rupture study our cohort consisted of 141 cases (ACL group) and 219 controls. Samples were genotyped for both the ELN rs2071307 and FBN2 rs331079 variants using TaqMan assays. Analysis of variance and chi-squared tests were used to determine whether either variant was associated with AT or ACL rupture with significance set at p<0.05. The GG genotype of the FBN2 variant was significantly over-represented within the TEN group (p=0.035; OR=1.83; 95% CI 1.04–3.25) compared to the CON group. We also found that the frequency of the G allele was significantly different between the TEN (p=0.017; OR=1.90; 95% CI 1.11–3.27) and ACL groups (p=0.047; OR=1.76; 95% CI 1.00–3.10) compared to controls. The ELN rs207137 variant was not associated with either AT or ACL rupture. In conclusion, DNA sequence variation within the FBN2 gene is associated with both AT and ACL rupture.
Keywords: gene; achilles tendinopathy; tendon rupture; ligament rupture; injury prevention